Biologia e manejo cultural das plantas daninhas Spermacoce densiflora DC. e Spermacoce verticillata L. (Rubiaceae) - Castilho, Juliana (2020)
The occurrence of the false buttonweed weed (Spermacoce densiflora DC. and Spermacoce verticillata L.) in agricultural areas, especially the known MATOPIBA region (Maranhão, Tocantins, Piauí and Bahia), has become a problem, since the area is considered one of the largest grain producers in Brazil. Field observations reported the lack of chemical control of these species. As a result, the present work aimed to understand how the biology of the species Spermacoce densiflora and Spermacoce verticillata, with variables related to germination and emergence, may contribute to the development of management strategies for these weeds. In this context, four experiments were developed. In the first, the influence of light and temperature on seed germination was studied, in a completely randomized design. Six temperatures (15, 20, 25, 30, 35 ° C and 20-30 ° C) and two light conditions (presence and absence of light) and a 12-hour photoperiod were studied. It was found that the species S. densiflora is photoblastic positive, as there was no germination in constant darkness. Regarding germination, S. verticillata found that the species is photoblastic neutral, however the germination of the species is favored by the presence of light. For both species, the highest percentage of germination and germination speed index were obtained under alternating temperature. In the second experiment, the effect of sowing depth on seedling emergence was evaluated. Seven sowing depths (0.0, 0.5, 1.0, 2.0, 4.0, 6.0 and 10.0 cm) were studied. The evaluation period was 42 days after sowing. The emergence of seedlings, of both species, was maximum when placed on the soil surface. From 0.5 cm deep, there was a significant decrease in seedling emergence, and the emergence rate was zero at a depth of 10.0 cm for both species. In the third experiment, the effects of different amounts of straw (half, as recommended and twice as recommended for use) on the surface of the cover plants were studied: Cajanus cajan (Guandu beans), Crotalaria juncea (Crotalaria), Dolichos lablab (Lablab), Pennisetum glaucum (Millet) and Sorghum bicolor (Sorghum), on the emergence of species. The fourth experiment evaluated the allelopathic potential of aqueous extracts from aerial parts of species used as green manure in different concentrations (20%, 40%, 60% and 100%) on seed germination. In addition, tests were performed with PEG-6000 in order to determine the influence of the osmotic potential of the extracts. The use of cover plants can be an alternative in the integrated management of false buttonweed weeds. There was no significant difference between the different amounts of straw used, however the use of half of the recommendation was the least effective. Millet and crotalaria outperform other cover crops. Regarding the experiment with extracts, with the increase in concentrations there was a reduction in the percentage and speed of germination for S. densiflora and S. verticillata, and the osmotic potential of the aqueous extracts of the aerial part, of the cover plants varied between -0, 37 MPa and -1.24 MPa. Considering that in the experiment with PEG-6000 there was no germination of weed seeds with an osmotic potential below -0.8 MPa and that the percentage of germination in treatments at -0.2MPa and -0.4 MPa were higher than the rates obtained in the experiment with aqueous extracts of cover plants, it can be inferred that, possibly, in this interval, there was an allelopathic effect of cover plants.